High-first-effect and low-stress silicon monoxide-based all-solid-state lithium battery
By prelithiating the silicon oxide negative electrode, the safety hazards of liquid electrolytes in traditional lithium-ion batteries and the problem of low Coulomb efficiency in the first circle of the silicon oxide negative electrode are solved, and a high-first-effect and low-stress silicon oxide base is achieved All solid state lithium battery.
Patent Information
- Application Number
- CN202411575179.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional lithium-ion batteries have safety hazards of liquid organic electrolytes, and the consumption of irreversible lithium in the first circle of silicon oxide negative electrode is large during the lithiation process of the first circle of silicon, resulting in low Coulomb efficiency in the first circle.
Prelithiation of silicon oxide by prelithiation technology, including lithium-copper composite belt in situ prelithium method, prelithiation additive method, self-discharge contact prelithiation method, chemical prelithiation method and electrochemical prelithization to reduce the consumption of irreversible lithium and improve the first-circle Coulomb efficiency of the battery.
The first-round Coulomb efficiency of the battery was significantly improved from 60% to 90% or above, and the combination of high first-line efficiency and low stress was achieved, overcoming the problem of low Coulomb efficiency of traditional silicon oxide materials in the first-round Coulomb efficiency in the battery. .
Smart Images

Figure CN119419369A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode pre-lithiation, and in particular to a high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in aerospace, mobile electronic devices, electric vehicles and many other fields due to their advantages such as high energy density, high power density and low self-discharge. Its internal working principle relies on the shuttling of lithium ions between the positive and negative electrodes inside the battery, and the energy conversion is completed by the movement of electrons in the external circuit. However, traditional lithium-ion batteries usually use liquid organic electrolytes, which inevitably have some safety hazards, such as easy leakage, easy combustion, easy explosion and other problems.
[0003] In contrast, all-solid-state lithium batteries use solid electrolytes, which are solid substances with ion conductivity and electronic insulation, mainly divided into oxides, polymers, halides, and sulfides. Solid electrolytes have many advantages, including high energy density, good cycle performance, long life, and a wide electrochemical window, and excellent mechanical properties can prevent the growth of lithium dendrites. Therefore, using solid electrolytes instead of liquid electrolytes can effectively solve the safety problems of liquid electrolytes, and all-solid-state lithium batteries have the characteristics of high energy density, high power density, and wide temperature adaptability.
[0004] Silicon dioxide is a non-equilibrium state composed of nano-sized Si clusters, SiO2 clusters and various interface sub-oxides bonded by Si-O bonds. It has a high theoretical specific capacity (~2043 mAh g -1 ), low cost and abundant reserves, so it is widely regarded as a promising negative electrode material. Compared with the problems of lithium dendrite growth caused by lithium metal anode and significant volume expansion (~300%) of silicon anode, silicon oxide anode can effectively avoid these problems. However, it will form irreversible lithium silicate phases (Li2SiO3, Li4SiO4, Li2Si2O5) and Li2O during the first cycle of lithiation. On the one hand, these irreversible phases can act as buffer matrices to reduce the volume change of silicon oxide during lithiation / delithiation. Therefore, compared with nano-silicon anode, silicon oxide has a smaller volume expansion rate (~200%), which makes it perform better in terms of long-cycle battery performance; on the other hand, the formation of these irreversible phases will lead to a large loss of lithium, resulting in a low first-cycle coulombic efficiency. Therefore, pre-lithiation of silicon oxide by appropriate pre-lithiation methods to reduce the consumption of irreversible lithium is crucial to improve the first-cycle coulombic efficiency and electrochemical performance of the battery. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and provide a high initial efficiency, low stress silicon oxide based all-solid-state lithium battery.
[0006] To achieve the above-mentioned purpose of the invention, the present invention provides a high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery, and the preparation method thereof is as follows:
[0007] A pre-lithiation method is introduced during the preparation of silicon oxide-based negative electrodes or during the assembly of lithium batteries. The pre-lithiation methods include in-situ pre-lithiation method of lithium-copper composite belts, pre-lithiation additive method, self-discharge contact pre-lithiation method, chemical pre-lithiation method and electrochemical pre-lithiation method.
[0008] In one embodiment, the preparation material of the silicon oxide-based negative electrode includes at least one of silicon oxide, coated silicon oxide, and nanostructured silicon oxide.
[0009] In one embodiment, the type of the silicon oxide-based negative electrode is one of a wet-coated electrode, a dry-process powder electrode, and a dry-process thin-film electrode.
[0010] In one embodiment, the assembled lithium battery is one of a sulfide all-solid-state battery, a halide all-solid-state battery, an oxide all-solid-state battery, and a polymer all-solid-state battery; the material of the positive electrode of the assembled lithium battery is one of a ternary material, lithium cobalt oxide, lithium iron phosphate, and elemental sulfur.
[0011] In one embodiment, the pre-lithiation gas atmosphere is one or more of argon, nitrogen, and helium, and the ambient dew point is lower than -20°C.
[0012] In one embodiment, the in-situ pre-lithiation method of the lithium-copper composite tape is to place a copper current collector with different lithium layer thicknesses at the bottom of the silicon oxide-based negative electrode during the battery assembly process, apply a pressure of 0 to 200 MPa, and keep it standing for 0 to 48 hours, so that the electrode and the lithium layer are spontaneously pre-lithiated, and the electrode loading is 0.1 to 200 mg cm -2 .
[0013] In one embodiment, the pre-lithiation additive method is to coat the pre-lithiation additive on the surface of the silicon oxide-based negative electrode, or add the pre-lithiation additive during the slurry preparation process in the wet coating process, so that the pre-lithiation additive is mixed with silicon oxide to obtain a silicon oxide-based negative electrode, and then assembled with the positive electrode and electrolyte into a lithium battery.
[0014] In one embodiment, the self-discharge contact pre-lithiation method is to contact the silicon oxide-based negative electrode and the lithium sheet in an electrolyte environment to form a short circuit, so that the electrolyte reacts on the electrode to pre-form a solid electrolyte interface, and then assemble it with the positive electrode and electrolyte into a lithium battery.
[0015] In one embodiment, the chemical pre-lithiation method is to pre-treat silicon oxide by immersing it in a lithium-containing organic solution or pre-treating silicon oxide by a chemical treatment method before battery assembly, and then prepare a silicon oxide-based negative electrode by a wet coating or dry electrode preparation method after pre-treatment, and then assemble it into a lithium battery with a positive electrode and an electrolyte.
[0016] In one embodiment, the electrochemical pre-lithiation method is to assemble a lithium sheet and a silicon oxide-based negative electrode into a half-cell, activate it, then disassemble and remove the silicon oxide-based negative electrode, clean and dry it, and then assemble it into a lithium battery with a positive electrode and an electrolyte.
[0017] The advantages and beneficial effects of the present invention over the prior art are as follows:
[0018] 1. The present invention significantly reduces the consumption of irreversible lithium in the first cycle of lithiation through pre-lithiation technology, and supplements reversible lithium to improve the first cycle coulomb efficiency of the battery. The first cycle coulomb efficiency of the half-cell can be increased from 60% to 90% or more, and the first cycle coulomb efficiency of the full cell can be increased from 60% to 85% or more.
[0019] 2. The present invention can obtain a high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery, which has the advantages of simple process, strong universality, and obvious effect.
[0020] 3. The present invention adopts pre-lithiation technology to overcome the challenge of low first-cycle coulombic efficiency faced by traditional silicon dioxide materials in the application of batteries, which is beneficial to improving the first-cycle coulombic efficiency and electrochemical performance of the battery, and realizes the combination of high first efficiency and low stress, which has important practical significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 This is the X-ray diffraction (XRD) pattern of silicon dioxide in Example 1 of the present invention.
[0023] Figure 2 is a scanning electron microscope (SEM) image of the silicon oxide composite negative electrode in Example 1 of the present invention;
[0024] Figure 3 This is a comparison diagram of the first cycle charge and discharge curves of the silicon oxide composite negative electrode||sulfide solid electrolyte||LiIn half-cell before and after pre-lithiation in Example 1 of the present invention;
[0025] Figure 4 It is a comparison diagram of the first cycle charge and discharge curves of the silicon oxide composite negative electrode||sulfide solid electrolyte||ternary NCM811 composite positive electrode full battery before and after pre-lithiation in Example 1 of the present invention;
[0026] Figure 5 This is a comparison chart of the first 20 cycles of the silicon oxide composite negative electrode||sulfide solid electrolyte||ternary NCM811 composite positive electrode full battery before and after pre-lithiation in Example 1 of the present invention;
[0027] Figure 6 It is a comparison chart of the first cycle charge and discharge curves of the lithium hydride pre-lithium silicon oxide negative electrode || LP33 || Li and the lithium hydride pre-lithium silicon oxide composite negative electrode || sulfide solid electrolyte || LiIn in Example 2 of the present invention.
[0028] Figure 7 This is a comparison chart of the first cycle charge and discharge curves of the lithium hydride pre-lithiation silicon dioxide composite negative electrode||sulfide solid electrolyte||ternary NCM811 composite positive electrode full battery before and after pre-lithiation in Example 2 of the present invention.
[0029] Figure 8 It is a comparison diagram of the first cycle charge and discharge curves of the silicon oxide composite negative electrode||sulfide solid electrolyte||LiIn half-cell before and after pre-lithiation in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The embodiment of the present invention provides a high initial efficiency, low stress silicon oxide based all-solid-state lithium battery, and the preparation method thereof is as follows:
[0032] A pre-lithiation method is introduced during the preparation of silicon oxide-based negative electrodes or during the assembly of lithium batteries. The pre-lithiation methods include in-situ pre-lithiation method of lithium-copper composite belts, pre-lithiation additive method, self-discharge contact pre-lithiation method, chemical pre-lithiation method and electrochemical pre-lithiation method.
[0033] The present invention reduces the consumption of irreversible lithium in the first lithiation process through pre-lithiation technology to improve the first coulomb efficiency of the battery. Pre-lithiation can not only reduce the consumption of irreversible lithium in the first lithiation process, but also improve the cycle performance to a certain extent. Suitable pre-lithiation methods should be selected according to the characteristics of different systems. For wet-coated electrodes, it is recommended to adopt self-discharge contact pre-lithiation method, chemical pre-lithiation method and electrochemical pre-lithiation method, and then assemble all-solid-state batteries. For dry powder electrodes and dry thin film electrodes, lithium copper composite belt in-situ pre-lithiation method or pre-lithiation additive method can be selected during the battery assembly process to avoid the influence of solvents used in other pre-lithiation methods on electrode performance. In the pre-lithiation process, the degree of pre-lithiation needs to be maintained within an appropriate range. If the degree of pre-lithiation is too low, the amount of lithium supplementation is insufficient, the pre-lithiation effect is not obvious, and it is difficult to significantly improve the first coulomb efficiency; on the contrary, if the degree of pre-lithiation is too high, it may cause lithium metal to remain on the surface of the negative electrode, thereby causing problems such as negative electrode lithium precipitation, lithium dendrite growth and short circuit. Therefore, pre-lithiation should be maintained within an appropriate range.
[0034] Furthermore, the preparation material of the silicon oxide-based negative electrode includes at least one of silicon oxide, coated silicon oxide, and nanostructured silicon oxide. Silicon oxide has the advantages of higher theoretical energy density, smaller volume expansion than silicon, and the ability to inhibit the growth of lithium dendrites, and silicon oxides of different structures may show different advantages in battery performance.
[0035] Furthermore, the type of the silicon oxide-based negative electrode is one of a wet coating electrode, a dry powder electrode, and a dry thin film electrode. Different electrode preparation methods have certain differences in cost, performance, and production process in the battery system. Choosing a suitable electrode preparation method is conducive to better performance of the battery.
[0036] Furthermore, the assembled lithium battery is one of a sulfide all-solid-state battery, a halide all-solid-state battery, an oxide all-solid-state battery, and a polymer all-solid-state battery. Different battery systems have different advantages. For example, sulfide batteries may have higher ion conductivity, while oxide batteries may be more stable, and polymer all-solid-state batteries can provide greater flexibility and lighter weight. The material of the positive electrode of the assembled lithium battery is one of ternary materials, lithium cobalt oxide, lithium iron phosphate, and sulfur. The positive electrode is a key material that determines the capacity of the battery.
[0037] Furthermore, the pre-lithiation gas atmosphere is one or more of argon, nitrogen, and helium, and the ambient dew point is lower than -20° C. During the pre-lithiation process, the dryness of the atmosphere needs to be controlled, and a low dew point gas environment helps ensure the effective progress of the lithiation reaction, thereby reducing side reactions that may be caused by moisture in the gas, thereby improving the overall stability and performance of the battery.
[0038] Furthermore, the in-situ pre-lithiation method of the lithium-copper composite tape is to place a copper current collector with different lithium layer thicknesses at the bottom of the silicon oxide-based negative electrode during the battery assembly process, apply a pressure of 0 to 200 MPa, and keep it standing for 0 to 48 hours, so that the electrode and the lithium layer are spontaneously pre-lithiated, and the electrode loading is 0.1 to 200 mg cm -2 This method promotes the migration and combination of lithium by controlling the mechanical pressure and the standing time, and can precisely control the distribution and amount of lithium, ensuring that the electrode obtains the required lithium source before use. The electrode loading is 0.1-200 mg cm -2 The appropriate loading can affect the energy density of the electrode and the overall performance of the battery. Too high or too low loading may lead to a decrease in the electrochemical performance of the battery, so precise control is required in the design.
[0039] Furthermore, the pre-lithiation additive method is to coat the pre-lithiation additive on the surface of the silicon oxide-based negative electrode, or add the pre-lithiation additive during the slurry preparation process in the wet coating process, so that the pre-lithiation additive is mixed with silicon oxide to obtain a silicon oxide-based negative electrode, and then assembled with the positive electrode and electrolyte into a lithium battery.
[0040] Pre-lithiation additives such as lithium metal powder, Li x Si powder, Li x Ge powder, etc.; This method can directly increase the lithium source of the negative electrode material, thereby improving the first coulombic efficiency of the battery. At the same time, the steps of adding a pre-lithiation additive during the slurry preparation process in the wet coating process, and mixing the pre-lithiation additive with silicon oxide to obtain a silicon oxide-based negative electrode are the same as the process of preparing a lithium hydride pre-lithiation silicon oxide negative electrode by the wet coating method in Example 2, except that the lithium hydride pre-lithiation silicon oxide in Example 2 is replaced with silicon oxide, and more pre-lithiation additives are added during the slurry formation process;
[0041] Furthermore, the self-discharge contact pre-lithiation method is to contact the silicon oxide-based negative electrode and the lithium sheet in an electrolyte environment to form a short circuit, so that the electrolyte reacts on the electrode to pre-form a solid electrolyte interface, and then assemble it with the positive electrode and electrolyte into a lithium battery. This method pre-generates a solid electrolyte interface SEI through spontaneous reaction, which can effectively inhibit the direct reaction between the electrolyte and the electrode material, thereby effectively improving the first-cycle coulomb efficiency and cycle stability of the battery.
[0042] Furthermore, the chemical pre-lithiation method is to pre-treat silicon oxide by immersing it in a lithium-containing organic solution or pre-treat silicon oxide by a chemical treatment method before battery assembly, and then prepare a silicon oxide-based negative electrode by a wet coating or dry electrode preparation method after pre-treatment, and then assemble it into a lithium battery with a positive electrode and an electrolyte.
[0043] Lithium-containing organic solutions such as n-butyl lithium, lithium-aromatic complexes, and lithium-biphenyl solutions; this method introduces lithium in advance through chemical reactions to enhance the conductivity and activity of the negative electrode, thereby improving the charge and discharge performance of the battery.
[0044] Furthermore, the electrochemical pre-lithiation method is to assemble the lithium sheet and the silicon oxide-based negative electrode into a half-cell, activate it, then disassemble and remove the silicon oxide-based negative electrode, clean and dry it, and then assemble it with the positive electrode and electrolyte into a lithium battery. This method can flexibly adjust the pre-lithiation conditions during the battery assembly process, thereby obtaining the best lithium distribution and optimizing the overall performance of the battery.
[0045] The present invention has been tested for many times, and some test results are now cited as references to further describe the invention in detail, and the following is a detailed description in conjunction with specific embodiments.
[0046] Example 1
[0047] The silicon oxide composite negative electrode was prepared. The entire preparation step was carried out in a glove box (the gas atmosphere was argon and the ambient dew point was below -20°C). The specific preparation method is as follows:
[0048] Weigh the following materials according to the mass ratio: silicon dioxide (SiO): sulfide solid electrolyte (Li 5.5 PS 4.5 Cl 1.5 ): conductive carbon fiber (VGCF): polytetrafluoroethylene (PTFE) = 60:30:10:0.5, wherein the XRD pattern of silicon oxide is as follows Figure 1 As shown; After weighing the above materials according to the ratio, mix the materials through a mixer, set the speed and time to 600rpm and 30min respectively. The fiberization of PTFE can be achieved by applying a certain shear force in a mortar, and then rolling it on a hot roller machine, and the rolling temperature range is 60℃~120℃. The thickness of the rolled pole piece can be measured by a micrometer. When the thickness is close to the required value, the required pole piece, i.e., the silicon oxide composite negative electrode, is obtained by a punching machine;
[0049] After obtaining the silicon oxide composite negative electrode, the following operations were performed in a glove box (gas atmosphere was argon, and the ambient dew point was below -20°C): assembling the silicon oxide composite negative electrode||sulfide solid electrolyte||LiIn half-cell, and the silicon oxide composite negative electrode||sulfide solid electrolyte||ternary NCM811 composite positive electrode full cell. The silicon oxide composite negative electrode was pre-lithiated, and the lithium copper composite tape was used for in-situ pre-lithiation. During the battery assembly process, a copper current collector with a lithium layer thickness of 5 μm was placed at the bottom of the silicon oxide composite negative electrode, and a pressure of 100 MPa was applied. After the battery was assembled, it was left to stand for 30 hours to ensure that the diffusion reaction of lithium ions could be completely carried out.
[0050] The SEM image of silicon oxide composite negative electrode is shown in Figure 2 As shown in the figure, the distribution of silicon oxide, sulfide solid electrolyte, VGCF, and fibrous PTFE can be seen. Among them, the particle size of silicon oxide is relatively large, belonging to the micron level; the particle size of sulfide solid electrolyte is relatively small, filling the gaps between particles; VGCF and PTFE both present fibrous structures, and it is obvious that the fibers of VGCF are thicker than those of PTFE.
[0051] The first cycle charge and discharge curves of the silicon oxide composite anode||sulfide solid electrolyte||LiIn half-cell before and after pre-lithiation are shown in Figure 2. Figure 3 As shown. The first cycle discharge capacity before pre-lithiation is 2310.87mAh g -1 , charging capacity 1538.44mAh g -1 , the first cycle Coulombic efficiency is 66.57%. In contrast, the first cycle discharge capacity after pre-lithiation is 1621.53 mAh g -1 , charging capacity 1443.41mAh g -1 , the first-cycle Coulombic efficiency can be increased to 89.02%, indicating that the in-situ pre-lithiation method of lithium-copper composite belt can effectively improve the first-cycle Coulombic efficiency of silicon oxide negative electrode.
[0052] The first cycle charge-discharge curve and cycle-capacity curve of the full battery before and after pre-lithiation of silicon dioxide composite anode||sulfide solid electrolyte||ternary NCM811 composite cathode are shown in Figure 2. Figure 4 and Figure 5 As shown. Before pre-lithium, the first cycle charging capacity is 234.7mAhg -1 , discharge capacity 144.4mAh g -1 The first cycle coulombic efficiency is 61.51%. After pre-lithiation, the first cycle charging capacity is 224.3mAh g -1 , discharge capacity 180.9mAh g -1 , the first cycle Coulombic efficiency can be increased to 80.65%. From the cycle-capacity curve, it can be seen that the capacity has been improved to a certain extent after pre-lithiation through this method, which further shows that the high first efficiency and low stress silicon oxide all-solid-state lithium battery can be obtained through the in-situ pre-lithiation method of lithium-copper composite tape.
[0053] Example 2
[0054] This embodiment is a chemical treatment method in a chemical pre-lithiation method to pre-treat silicon oxide to prepare lithium hydride pre-lithiation silicon oxide. The preparation method is as follows: lithium hydride and silicon oxide are mixed according to a mass ratio of lithium hydride: silicon oxide = 12:100, and after mixing, they are placed in a box furnace, heated to 640°C under a nitrogen atmosphere, and kept warm for 1 hour to obtain lithium hydride pre-lithiation silicon oxide;
[0055] Utilize lithium hydride pre-lithiation silicon oxide, adopt dry electrode preparation method to prepare lithium hydride pre-lithiation silicon oxide composite negative electrode, adopt wet coating preparation method to prepare lithium hydride pre-lithiation silicon oxide negative electrode. Among them, the steps of preparing lithium hydride pre-lithiation silicon oxide composite negative electrode are the same as the steps of preparing silicon oxide composite negative electrode in the above-mentioned embodiment 1, only need to replace silicon oxide with lithium hydride pre-lithiation silicon oxide. Then in the glove box (the gas atmosphere is argon, and the ambient dew point is lower than -20°C), the lithium hydride pre-lithiation silicon oxide composite negative electrode prepared in this step is assembled into a solid-state battery to obtain lithium hydride pre-lithiation silicon oxide composite negative electrode||sulfide solid electrolyte||LiIn;
[0056] The process of preparing lithium hydride pre-lithiation silicon oxide negative electrode by wet coating method is as follows: first weigh according to the mass ratio, where lithium hydride pre-lithiation silicon oxide: conductive carbon black (Super P): single-walled carbon nanotube (CNT): sodium alginate (SA) = 94:3:1:2. After weighing, the lithium hydride pre-lithiation silicon oxide and Super P are pre-grinded evenly in a mortar, and then the remaining materials are added. Then, stir for a certain time by a Thinky disperser to obtain a uniform slurry. Subsequently, the slurry is coated on a copper foil using a 50μm scraper. After coating, the solvent is first blown to dry, and then it is transferred to a vacuum oven and baked overnight at 120°C to obtain a lithium hydride pre-lithiation silicon oxide negative electrode. Next, the liquid battery was assembled in a glove box (the gas atmosphere was argon and the ambient dew point was below -20°C). The electrolyte used was a lithium battery-specific electrolyte (LP33), and a 1mm lithium sheet was used as the counter electrode to prepare a lithium hydride pre-lithium silicon oxide negative electrode ||LP33||Li;
[0057] The first cycle charge and discharge curves of lithium hydride pre-lithiation silicon oxide anode||LP33||Li and lithium hydride pre-lithiation silicon oxide composite anode||sulfide solid electrolyte||LiIn are shown in Figure 6 As shown. In the liquid battery, the first cycle discharge capacity is 969.34 mAh g -1 , charging capacity 638.73mAh g -1 , the first cycle Coulombic efficiency is only 65.89%. In contrast, in solid-state batteries, the first cycle discharge capacity is 1003.80 mAh g -1 , charging capacity 792.91mAh g -1 , the first-cycle Coulombic efficiency can be increased to 78.99%. This result shows that the application of lithium hydride pre-lithiation silicon oxide in solid-state batteries can significantly improve the first-cycle Coulombic efficiency.
[0058] The first cycle charge and discharge curves of the full battery before and after pre-lithiation of lithium hydride pre-lithiation silicon oxide composite anode||sulfide solid electrolyte||ternary NCM811 composite cathode are shown in Figure 2. Figure 7Before pre-lithiation (same as silicon oxide composite negative electrode||sulfide solid electrolyte||ternary NCM811 composite positive electrode full battery in Example 1), the first cycle charging capacity is 232.32 mAh g -1 , the discharge capacity is 145.50mAh g -1 , the first cycle coulombic efficiency is 62.63%. After pre-lithiation (lithium hydride pre-lithiation silicon oxide composite negative electrode||sulfide solid electrolyte||ternary NCM811 composite positive electrode), the first cycle charging capacity is 231.12mAh g -1 , the discharge capacity is 186.06 mAh g -1 , the first-cycle Coulombic efficiency rose to 80.50%. This result further verifies the effectiveness of the application of lithium hydride pre-lithiation silicon oxide in solid-state batteries, which can significantly improve the first-cycle Coulombic efficiency.
[0059] Example 3
[0060] The process of preparing lithium hydride pre-lithiation silicon oxide negative electrode by wet coating method in implementation 2 is the same, only the lithium hydride pre-lithiation silicon oxide is replaced with silicon oxide, and after the silicon oxide negative electrode is obtained, it is subjected to self-discharge contact pre-lithiation, specifically: place it in a glove box (the gas atmosphere is argon, and the ambient dew point is lower than -20°C) and drip 10-100μL of LP33 on the electrode to make the electrode fully infiltrated, and then directly contact the lithium sheet with it. Apply 5MPa pressure and keep it still for 10min, then use dimethyl carbonate (DMC) solution to clean and dry it to obtain a self-discharge contact pre-lithiation silicon oxide negative electrode;
[0061] In a glove box (gas atmosphere is argon, ambient dew point is below -20°C), self-discharge contact pre-lithiation silicon oxide anode||sulfide solid electrolyte||LiIn half-cell and self-discharge contact pre-lithiation silicon oxide anode||sulfide solid electrolyte||ternary NCM811 composite positive electrode full cell were assembled. Compared with silicon oxide anode||sulfide solid electrolyte||LiIn half-cell and silicon oxide anode||sulfide solid electrolyte||ternary NCM811 composite positive electrode full cell that have not been pre-lithiated, the first cycle coulombic efficiency of the half-cell obtained by the self-discharge contact pre-lithiation method can be increased from 60% to 85% or more, and the first cycle coulombic efficiency of the full cell can be increased from 60% to 80% or more.
[0062] Example 4
[0063] The process of preparing lithium hydride pre-lithiation silicon oxide negative electrode by wet coating method in implementation 2 is the same, only the lithium hydride pre-lithiation silicon oxide is replaced with silicon oxide, and after the silicon oxide negative electrode is obtained, it is electrochemically pre-lithiated, specifically: it is placed in a glove box (the gas atmosphere is argon, and the ambient dew point is lower than -20°C), the silicon oxide negative electrode is assembled into a lithium half-cell, the electrolyte is LP33, and it is activated by a small current of 0.05C for one cycle. Subsequently, the battery is disassembled, the silicon oxide negative electrode is taken out, and the silicon oxide negative electrode is cleaned and dried by DMC solution to obtain an electrochemical pre-lithiation silicon oxide negative electrode;
[0064] Electrochemical pre-lithiation silicon oxide anode||sulfide solid electrolyte||LiIn half-cell and electrochemical pre-lithiation silicon oxide anode||sulfide solid electrolyte||ternary NCM811 composite cathode full cell were assembled in a glove box (gas atmosphere was argon, ambient dew point was below -20°C). Compared with the half-cell of silicon oxide anode||sulfide solid electrolyte||LiIn half-cell and silicon oxide anode||sulfide solid electrolyte||ternary NCM811 composite cathode full cell without pre-lithiation, the first cycle coulombic efficiency of the half-cell obtained by the electrochemical pre-lithiation method can be increased from 60% to 90% or more, and the first cycle coulombic efficiency of the full cell can be increased from 60% to 85% or more.
[0065] Comparative Example 1
[0066] The lithium copper composite tape with a lithium layer thickness of 5 μm was changed to 20 μm, and other operations were the same as in Example 1. The first cycle charge and discharge curve of the silicon oxide composite negative electrode||sulfide solid electrolyte||LiIn half-cell after pre-lithiation is as follows Figure 8 After pre-lithiation, the first cycle discharge capacity is 715 mAh g -1 , charging capacity is 1420mAh g -1 , the first cycle Coulombic efficiency is 198.54%. This result shows that the degree of pre-lithiation is too high.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high initial efficiency, low stress silicon oxide based all-solid-state lithium battery, characterized in that: Its preparation method is: A pre-lithiation method is introduced during the preparation of silicon oxide-based negative electrodes or during the assembly of lithium batteries. The pre-lithiation methods include in-situ pre-lithiation method of lithium-copper composite belts, pre-lithiation additive method, self-discharge contact pre-lithiation method, chemical pre-lithiation method and electrochemical pre-lithiation method.
2. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The preparation material of the silicon oxide-based negative electrode includes at least one of silicon oxide, coated silicon oxide, and nanostructured silicon oxide.
3. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The type of the silicon oxide-based negative electrode is one of a wet coating electrode, a dry powder electrode, and a dry thin film electrode.
4. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The assembled lithium battery is one of a sulfide all-solid-state battery, a halide all-solid-state battery, an oxide all-solid-state battery, and a polymer all-solid-state battery; the material of the positive electrode of the assembled lithium battery is one of a ternary material, lithium cobalt oxide, lithium iron phosphate, and elemental sulfur.
5. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The gas atmosphere for pre-lithiation is one or more of argon, nitrogen and helium, and the ambient dew point is lower than -20°C.
6. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The in-situ pre-lithiation method of the lithium-copper composite tape is to place a copper current collector with different lithium layer thicknesses at the bottom of the silicon oxide-based negative electrode during the battery assembly process, apply a pressure of 0 to 200 MPa, and keep it still for 0 to 48 hours, so that the electrode and the lithium layer are spontaneously pre-lithiated, and the electrode loading is 0.1 to 200 mg cm -2 .
7. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The pre-lithiation additive method is to coat the pre-lithiation additive on the surface of the silicon oxide-based negative electrode, or add the pre-lithiation additive during the slurry preparation process in the wet coating process, so that the pre-lithiation additive is mixed with silicon oxide to obtain a silicon oxide-based negative electrode, and then assembled with the positive electrode and electrolyte into a lithium battery.
8. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The self-discharge contact pre-lithiation method is to contact the silicon oxide-based negative electrode and the lithium sheet in an electrolyte environment to form a short circuit, so that the electrolyte reacts on the electrode to pre-form a solid electrolyte interface, and then assemble it with the positive electrode and electrolyte into a lithium battery.
9. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The chemical pre-lithiation method is to pre-treat silicon oxide by immersing it in a lithium-containing organic solution or by chemical treatment before assembling the battery, and then prepare a silicon oxide-based negative electrode by wet coating or dry electrode preparation method after pretreatment, and then assemble it into a lithium battery with a positive electrode and an electrolyte.
10. The high initial efficiency, low stress silicon oxide-based all-solid-state lithium battery according to claim 1, characterized in that: The electrochemical pre-lithiation method is to assemble a lithium sheet and a silicon oxide-based negative electrode into a half-cell, activate it, then disassemble and remove the silicon oxide-based negative electrode, clean and dry it, and then assemble it with a positive electrode and an electrolyte into a lithium battery.
Citation Information
Patent Citations
Pre-lithiation device and method for lithium ion battery negative electrode pole piece with controllable pre-lithiation degree
CN109524621A
Negative electrode material, negative electrode plate, preparation method of negative electrode plate and all-solid-state lithium ion battery
CN111430681A
Device for chemical pre-lithiation of aromatic hydrocarbons
CN112563458A
Method for improvingfirst coulombic efficiency by pre-lithiating silicon monoxide negative electrode of lithium ion battery
CN113594416A
Preparation method of pre-lithiated negative plate of lithium ion battery
CN117476877A
Cited By
Composite negative electrode, preparation method thereof and application of composite negative electrode in all-solid-state battery
CN122370311A
Composite negative electrode, preparation method thereof and application thereof in all-solid-state battery
CN122370311B